Non-Gaussian surface parameters effects on Micro-TEHL performance and surface stress of aero-engine main-shaft ball bearing. (April 2016) - Shi, Xiu-Jiang; Wang, Li-Qin; Qin, Fen-Qi
Abstract: In this paper, aero-engine main-shaft ball bearing is for research, firstly, bearing quasi-dynamics is applied to acquire the mechanical and kinematic parameters, then non-Gaussian surface roughness is simulated based on digital filter technique, finally, micro-TEHL analysis is carried out by multi-grid method. Non-Gaussian surface parameters effects on micro-THEL performance and surface stress are discussed. The minimum film thickness, maximum film temperature, maximum film pressure and maximum shear stress under different non-Gaussian parameters are given, and the transition points of mixed lubrication state are pointed out. Highlights: We propose a combined method of quasi-dynamics, surface simulating and micro-TEHL analysis. We set up a coupled numerical model for lubrication and stress analysis of ball bearing. Non-Gaussian parameters effects on micro-TEHL performance were researched. The transition points of mixed lubrication state are pointed out.